2013
DOI: 10.1371/journal.pone.0072792
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Duct Patterns in Acute Pancreatitis: A MRI Study

Abstract: ObjectivesTo study the MRI findings of the pancreatic duct in patients with acute pancreatitis.Materials and MethodsA total of 239 patients with acute pancreatitis and 125 controls were analyzed in this study. The severity of acute pancreatitis was graded using the MR severity index (MRSI) and the Acute Physiology And Chronic Healthy Evaluation II(APACHE II) scoring systems. The number of main pancreatic duct (MPD) segments visualized, and both MPD diameter and pancreatic duct disruption were noted and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…MRI Abdomen. MRI abdomen without and with IV contrast with MRCP has comparable diagnostic and prognostic value to CT abdomen without and with IV contrast in AP [22] and can be used to assess the severity of AP and its local complications. An MRI severity index based on the degree of pancreatic and peripancreatic fluid and the extent of pancreatic necrosis significantly correlates with CT severity index, the clinical variables associated with the severity of AP, and the clinical outcome [22].…”
Section: Special Imaging Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI Abdomen. MRI abdomen without and with IV contrast with MRCP has comparable diagnostic and prognostic value to CT abdomen without and with IV contrast in AP [22] and can be used to assess the severity of AP and its local complications. An MRI severity index based on the degree of pancreatic and peripancreatic fluid and the extent of pancreatic necrosis significantly correlates with CT severity index, the clinical variables associated with the severity of AP, and the clinical outcome [22].…”
Section: Special Imaging Considerationsmentioning
confidence: 99%
“…MRI abdomen without and with IV contrast with MRCP has comparable diagnostic and prognostic value to CT abdomen without and with IV contrast in AP [22] and can be used to assess the severity of AP and its local complications. An MRI severity index based on the degree of pancreatic and peripancreatic fluid and the extent of pancreatic necrosis significantly correlates with CT severity index, the clinical variables associated with the severity of AP, and the clinical outcome [22]. Local complications seen on MRI in the acute period (48-72 hours after symptom onset), such as pararenal space involvement, gallbladder abnormalities, and visible pancreatic duct disruption, correlate with the severity of AP according to MRI severity index and may be supplementary signs of AP severity [22][23][24].…”
Section: Special Imaging Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that as the severity increases, the incidence of pancreatic duct rupture also increases. The development of a disruption and a ruptured pancreatic duct on the MRI scan can be another credible indicator of the severity of acute pancreatitis (43), and the severity determines the clinical treatment method and predicts the short-term and long-term complications.…”
Section: Disconnected Pancreatic Duct Syndrome (Dpds)mentioning
confidence: 99%
“…The greater the flexion of the main pancreatic duct, the greater the possibility of the occurrence of AP. The incidence of pancreatic duct rupture increases with the severity of AP and can be used as another simple auxiliary index to assess and predict the severity of AP (43). In terms of clinical treatment, surgical indications and the timing of the surgery are important for patients who require surgical intervention.…”
Section: Mri For the Severity Of Acute Pancreatitismentioning
confidence: 99%